Approach to a cerebral hernia caused by an intratumoral hemorrhage of a cystic oligodendroglioma: a case report - Zhou, Jiahua; Wu, Yingxi; Qin, Huaizhou; Wang, Shoujie; Feng, Dayun; Yang, Di (Frontiers in Oncology, 2024)
The incidence of cerebral herniation caused by intratumoral hemorrhage (ITH) in cystic oligodendroglioma (COD) is exceedingly rare. This study presents a case of cerebral herniation subsequent to cystic oligodendroglioma (COD) and sudden intratumoral hemorrhage. Following initial emergency treatment and evaluation, we successfully circumvented the solid component of the tumor and proceeded with cystic puncture and external drainage to prevent the incidence of brain herniation and mitigate the severity of associated symptoms. Based on preoperative examination results, the cystic glioma was successfully resected, and the patient experienced an uneventful recovery. According to the pathological findings, the oligodendroglioma was classified as World Health Organization (WHO) grade III. The treatment efficacy was comparable to cases of the same pathological grade, in which neither intratumoral hemorrhage nor cerebral hernia was observed.